Sosialisasi Digital Marketing Menuju UMKM Kreatif Desa Karangrejo Kecamatan Gumukmas Kabupaten Jember - Fatmah Rahmawati, Olga; Wahyu Prasetyo, Lucky; Maulana, Adam; Lanza, Alviano; Titi Hapsari, Yusita (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract: This collaborative goal of the KKN program is to advance community development through the use of science and technology, as well as enhancing and developing the community's contributing to the local economy through business management and marketing strategies for small and medium-sized businesses in Karangrejo Village, Gumukmas subdistrict, Jember district. One of the Collaborative KKN group 013 work programs is holding MSME socialization activities which is the first step to educate and provide more insight to MSME actors or the wider community. This socialization carried out in order to improve marketing volume of the business it owns. This socialization raised the theme "Socialization of Packaging and Branding of MSME Products in the Era of Digitalization". In this socialization, it is divided into one material, namely about motivation for branding and marketing as well as direction for halal certification. In this socialization, we from Collaborative KKN group 013 brought in a speaker from outside who is more experienced in their field. The speaker was Mr. Aries Nugroho as a PLUT KUKM consultant for Jember district. Also working with Mrs. Zaenab who is an MSME actor and also the owner of banana chips and tempeh. She started the business in 2011. Although Mrs. Zaenab herself has experienced the ups and downs of building a business and even went bankrupt. Mrs. Zaenab herself also has a lot of experience as a mentor for micro businesses in the Karangrejo village environment. Keyword: Digital Marketing Socialization, UMKM Karangrejo Village, KKN Collaboration